Hydro-chemical characteristics and evaluation of water quality for irrigation purposes in the Madukismo Sugar Factory Area, Kasihan, Bantul - Artiwiputri, Hayuning Endraswari; Pulungan, Nur Ainun Harlin Jennie; Gunadi, Rahmat (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
River water is crucial for irrigation requirements although it may be jeopardized by both natural phenomena and anthropogenic activity. The rice fields in Mrisi Hamlet, Tirtonirmolo, Bantul are irrigated by water sourced from the vicinity of the Madukismo sugar factory. This raises worries on the contamination of irrigation water by waste from sugar factories, which would subsequently affect rice fields. This study aimed to (i) examine the quality and hydro-chemical features of irrigation water in the study region, and (ii) investigate the impact of irrigation water on NPK concentration in soil and rice yield. The employed research approach is descriptive quantitative. Laboratory analysis was conducted on samples of water, soil, and vegetation. The analysis of water samples was conducted at the source areas, as well as at the inlet, middle, and outflow points of the tertiary irrigation channel traversing the rice fields. Samples were collected from rice fields irrigated with uncontaminated water and those contaminated by sugar industry effluent. The evaluation of irrigation water quality is founded on PP No. 22 of 2021. A statistical study using the ANOVA test was conducted to evaluate plant development across different locales. The study's results indicated a considerable disparity in irrigation air quality between contaminated and unpolluted areas, as evidenced by the metrics of air temperature, total dissolved solids (TDS), chemical oxygen demand (COD), and biological oxygen demand (BOD). The quality of irrigation water contaminated by sugar industry effluent surpassed the established maximum limit for irrigation water. Nevertheless, the waste from the Madukismo sugar refinery positively influenced plant output. The growth and productivity of rice plants on contaminated soil exceeded those on unpolluted land. The rice yield in the contaminated region was 8,000 kg/Ha, higher than in the control area, which yielded just 4,800 kg/Ha.